Rancang Bangun Fault Tolerance pada Sistem Database untuk Aplikasi Point Of Sale - Standy Oei; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
Abstract— A fault tolerant system is a system that has the ability to be able to continue its jobs properly although there is a fault in hardware or software of the system. A system that has a fault tolerant capability is usually critical or important system. For example is at Point Of Sale application. Point Of Sale Application has evolved from offline-based toward online-based. With an online-based, the existence of a central database server must be guaranteed free from failure.To get a central database server that is free from failure is impossible. Something that can be cultivated is to create a system that can tolerate a failure in the central database server. This is done with the help of a second central database server (slave), which is useful as a replication of the central database server (master). To ensure data from these two central database servers are the same, then used the concept of reading and writing